1, 3-Dipolar cycloaddition approach to novel dispiro[pyrazolidine-4, 3'-pyrrolizidine-2', 3''-indoline]-2'', 3, 5-triones. (1st June 2017) - Hussein, Essam; Ahmed, Saleh; El Guesmi, Nizar; Khairou, Khalid
A simple and convenient 1, 3-dipolar cycloaddition of non-stabilised azomethine ylides derived from isatins and L-proline, in a variety of different solvents, to (Z)-4-arylidene-1-phenylpyrazolidine-3, 5-diones as dipolarophiles afforded a series of novel dispiro[pyrazolidine-4, 3'-pyrrolizidine-2', 3''-indoline]-2'', 3, 5-triones regioselectively and in good yields.